Influence of carbon content on microstructure and properties of a steel matrix cermet. (September 2018) - Alvaredo, P.; Bruna, P.; Crespo, D.; Gordo, E.
Abstract: There is a marked correlation between the composition, microstructure and properties in TiCN-based cermets. In the case of using iron alloys as metallic matrix the carbon content is of particular significance, as not only influences the stoichiometry of ceramic phase but also induces phase transformations in the steel matrix. However, such influence has been less studied in steel matrix cermets than in conventional Ni or Co ones, so the aim of this work is to contribute to the study of the influence of carbon content on the microstructure and properties of a steel matrix cermet containing fixed quantities of alloying elements. Samples were prepared by powder metallurgy and characterized combining different techniques as Transmission Mössbauer spectroscopy (TMS), X Ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM) and transmission electron microscopy (TEM), to explain differences found in hardness and toughness. Highlights: Large increase in hardness and toughness by increasing carbon content. Appearance of austenite and increase of martensite by increasing carbon content. Presence of solid solution (Ti, M)(C, N) resembling the typical core-rim structure.